Archaeological Research in the Našlaičiai Cemetery (Vilnius City) – Searches for the Remains of Lithuanian Partisans - Vėlius, Gintautas (Archaeologia Lituana, 2021)
The article describes the archaeological research of the Našlaičiai (Orphans’) Cemetery in Vilnius carried out over the period of 2017–2020. The remains of the Lithuanian post-war partisans shot in the KGB Internal Prison between 1956 and 1963 had been searched for more than a decade. Only in 2016 the historian D. Indrišionis suggested a solid hypothesis, based on archival documents and documented facts, that the remains of the partisans could be hidden together with the bodies of the executed criminals in the Našlaičiai Cemetery, then operating in the suburbs of Vilnius. Performed archaeological research confirmed this version, and the remains of all the partisans shot in the Vilnius KGB Internal Prison during the mentioned time period were found in the cemetery. The article presents a brief history of the Našlaičiai Cemetery, analyses the archival sources and methodology used in the research, and provides a detailed description of the course and the results of the archaeological research.
Keywords: Našlaičiai (Orphans’) Cemetery; partisans; remains; forensic archaeology; KGB